Combining CGE and microsimulation models: Effects on equality of VAT reforms - Turid Åvitsland; Jørgen Aasness (Statistics Norway, Research Department, 2004)
The effects on the degree of equality of reforms in indirect taxation are analysed by using a microsimulation model of the Norwegian economy subsequent to a CGE model. The two main reforms studied are substitution of a uniform VAT rate on all goods and services and substitution of the non-uniform Norwegian VAT reform of 2001 for the previous, differentiated system. A main characteristic of the non-uniform reform is the halving of the VAT rate on food. All reforms are made public revenue neutral by changes in the VAT rate. Producer prices, pre-tax nominal incomes, wealth and transfers are all exogenous in the microsimulation model. In this paper we feed percentage changes in corresponding variables from the CGE model into the microsimulation model in order to enrich the microsimulation analyses. The non-uniform VAT reform leads to a clear increase in equality while the change in equality concerning the uniform reform is close to 0. With the uniform VAT reform, as opposed to the non-uniform, decompositions show that taking CGE effects into account has a large impact on the degree of equality. Changed producer prices and changed pre-tax nominal incomes, wealth and transfers both contribute to this.
Keywords: D3; D58; D61; D63; H2; 330; CGE and microsimulation models; "Macro-micro" links; Indirect taxation; VAT reforms; Equality